The effect of left atrial appendage closure on heart failure biomarkers: A PRAGUE-17 trial subanalysis - Herman, Dalibor; Osmancik, Pavel; Neuzil, Petr; Hala, Pavel; Lekesova, Veronika; Benesova, Klara; Hozman, Marek; Jarkovsky, Jiri; Novackova, Martina; Widimsky, Petr; Reddy, Vivek Y (Journal of cardiovascular electrophysiology, 2021)
INTRODUCTION: The randomized PRAGUE-17 trial demonstrated noninferiority of left atrial appendage closure (LAAC) to non-vitamin K anticoagulants (NOACs) for the prevention of major cardiovascular or cerebrovascular events. However, the left atrial appendage is an important source of natriuretic peptides and plays a role in left atrial reservoir function. Changes of heart failure (HF) biomarkers after LAAC compared to NOAC has not been studied. The aim of the study was to compare the changes in concentrations of HF biomarkers between LAAC and NOAC patients. METHODS: Of 402 patients randomized in the PRAGUE-17 trial, biomarkers were analyzed in 144 patients (73 in the NOAC and 71 in the LAAC group). Both groups had similar baseline characteristics. Serum concentration of NT-proBNP, NT-proANP, Galectin-3, and GDF-15 were measured at baseline (before the procedure in the LAAC group), at the 6-month (and at 24-month for NT-proBNP) follow-up timepoint. RESULTS: There were no significant differences in baseline, 6 month, and delta (δ = baseline - 6 month) concentrations of NT-proANP between the groups (NOAC: baseline 2.6 [0.5; 4.9], 6-month 3.1 [1.8; 4.8], p = .068; LAAC: baseline 3.3 [1.1; 4.6], 6-month 2.6 [0.9; 5.3], p = .51; p value for δ in concentrations between groups = 0.42). Similarly, there were no significant differences in baseline, 6, 24 months, and delta concentrations of NT-proBNP between the groups (NOAC: baseline 461.0 [113.5; 1342.0], 6 month 440.0 [120.5; 1291.5], 24 month 798 [274; 2236], p = .39; LAAC: baseline 421.0 [100.0; 1320.0], 6 month 601.0 [145.0; 1230.0], 24 month 855 [410; 1367], p = .28; p value for δ in concentrations between groups = 0.73 at 6 months, and 0.58 at 24 months). Finally, no significant differences were present in baseline, 6 month, and δ concentrations of Galectin-3 and GDF-15 between the two groups. CONCLUSION: LAAC did not significantly influence the levels of HF biomarkers 6 months after the procedure.
Keywords: fibrilace síní; Administration, Oral; cévní mozková příhoda; Atrial Appendage; lidé; antikoagulancia; Anticoagulants; Atrial Fibrillation; síňové ouško; Biomarkers; Heart Failure; aplikace orální; srdeční selhání; biologické markery; Humans; Stroke